2019
DOI: 10.1111/btp.12629
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity with primary forest determines the value of secondary tropical forests for bird conservation

Abstract: Species extinctions caused by the destruction and degradation of tropical primary forest may be at least partially mitigated by the expansion of regenerating secondary forest. However, the conservation value of secondary forest remains controversial, and potentially underestimated, since most previous studies have focused on young, single-aged, or isolated stands. Here, we use point-count surveys to compare tropical forest bird communities in 20-120-year-old secondary forest with primary forest stands in centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 82 publications
2
21
0
Order By: Relevance
“…These results reinforce previous findings highlighting the value of extensive forest patches in providing source populations of forest‐dependent bird species (Mayhew et al. ), thereby enriching the surrounding matrix via a spillover of ecosystem services, such as pollination, pest control, and seed dispersal. Spillover of services has been widely documented for a range of taxa (Tscharntke et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results reinforce previous findings highlighting the value of extensive forest patches in providing source populations of forest‐dependent bird species (Mayhew et al. ), thereby enriching the surrounding matrix via a spillover of ecosystem services, such as pollination, pest control, and seed dispersal. Spillover of services has been widely documented for a range of taxa (Tscharntke et al.…”
Section: Discussionsupporting
confidence: 91%
“…populations of forest-dependent bird species (Mayhew et al 2019), thereby enriching the surrounding matrix via a spillover of ecosystem services, such as pollination, pest control, and seed dispersal. Spillover of services has been widely documented for a range of taxa (Tscharntke et al 2012), including insect and bird pollinators (Renjifo 2001;Ricketts et al 2008), and bird spillover has been shown to be particularly important in coffee plantations (Boesing et al 2018a), where birds control populations of pests (Johnson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It can take many decades for a forest to mature, and colonization by specialist bird species is likely to take much more than 20 years (Catterall et al, ; Freeman et al, ). Recent results from a chronosequence (20–120 years) of secondary tropical forests in Panana suggest that connectivity with extensive primary forest is a more important determinant of bird species richness than forest age (Mayhew, Tobias, Bunnefeld, & Dent, ), therefore the effect of landscape context in our study warrants further investigation.…”
Section: Discussionmentioning
confidence: 81%
“…Recent results from a chronosequence (20-120 years) of secondary tropical forests in Panana suggest that connectivity with extensive primary forest is a more important determinant of bird species richness than forest age (Mayhew, Tobias, Bunnefeld, & Dent, 2019), therefore the effect of landscape context in our study warrants further investigation.…”
Section: F I G U R E 1mentioning
confidence: 93%
“…The understanding of fire ecology in this ecosystem is very important, since predictions for climatic change in the region foresee increases in mean temperatures that could, in turn, increase fire occurrence and effects (Scholze et al 2006;Flannigan et al 2009). Under this scenario, remnant undisturbed forests could be key to helping preserve biodiversity in the region and to designing appropriate conservation strategies (Mayhew et al 2019). These strategies will help assure a continuous provision of ecosystem services in a changing climate.…”
Section: Introductionmentioning
confidence: 99%